2012
DOI: 10.1194/jlr.m026823
|View full text |Cite
|
Sign up to set email alerts
|

ACAT2 and ABCG5/G8 are both required for efficient cholesterol absorption in mice: evidence from thoracic lymph duct cannulation

Abstract: This article is available online at http://www.jlr.org Beginning in 1974, the identifi cation of sitosterolemia ( 1 ), a rare recessive disorder characterized by elevated plasma and tissue concentrations of phytosterols, has focused attention on the basic molecular processes that govern how the body normally absorbs animal-derived dietary cholesterol while excluding all other similarly structured plantderived sterols, generally called phytosterols. Phytosterols, including campesterol, stigmasterol, and sitoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Because G5/G8 is presumed to efflux sterols into the intestinal lumen, its deficiency would expectedly accumulate cholesterol in the mucosa. Also, since G5/G8 is expressed differentially along the length of the intestine [42], which is thought to contribute to differential degrees of absorption [20,21,43], we speculated that G5/G8 deficiency would accumulate lipids differently in the various intestinal segments. However, we found that G5/G8 deficiency did not affect the mucosal accumulation of cholesterol, except slightly in the duodenum (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because G5/G8 is presumed to efflux sterols into the intestinal lumen, its deficiency would expectedly accumulate cholesterol in the mucosa. Also, since G5/G8 is expressed differentially along the length of the intestine [42], which is thought to contribute to differential degrees of absorption [20,21,43], we speculated that G5/G8 deficiency would accumulate lipids differently in the various intestinal segments. However, we found that G5/G8 deficiency did not affect the mucosal accumulation of cholesterol, except slightly in the duodenum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to sterol absorption, G5/G8 is well-established to limit the absorption of plant sterols [6,11,12,[19][20][21]. However, the extent to which G5/G8 limits cholesterol absorption is unclear.…”
mentioning
confidence: 99%
“…Inside the enterocytes, the cholesterol is reesterifi ed by ACAT2, packaged with triglyceride and apoB-48 into chylomicrons by microsomal triglyceride transfer protein (MTTP), and then secreted into the circulation ( 22 ). Additionally, the ATP binding cassette transporter proteins ABCG5 and ABCG8 have been shown to be involved in resecretion of the enterocyte cholesterol back into the lumen ( 23,24 ). Other factors, including the rate of gastric emptying, have been shown to alter the rate of cholesterol absorption between inbred mouse strains ( 25 ).…”
Section: H]cholesterol Absorption and Secretionmentioning
confidence: 99%
“…Along the apical membrane of enterocytes, the heterodimer ABCG5/G8 counteracts the NPC1L1-mediated sterol uptake (29)(30)(31)(32) by promoting FC effl ux back into the intestinal lumen, with the net result of cholesterol absorption inhibition. Thoracic lymph duct cannulation studies have provided clear evidence that effi cient cholesterol absorption requires both ACAT2 and ABCG5/G8 heterodimer, with the latter being responsible for the apical effl ux of newly absorbed FC into the gut lumen, thus limiting the substrate availability for the esterification reaction ( 27 ).…”
Section: Intestinal Regulation Of Hdl Cholesterolmentioning
confidence: 99%
“…FC is soluble in membrane phospholipids and represents an important structural component of cellular membranes; by contrast, CE is mostly insoluble in membranes and must be packaged into lipid droplets or incorporated into the core of lipoprotein particles for export out of the cell. Studies in ACAT2 knockout mice have reported that the lack of CE formation results in reduced cholesterol absorption ( 24,25 ), and that CE formation by ACAT2 selectively utilizes chylomicron particles for quantitative transport of newly absorbed cholesterol out of the enterocyte into the lymphatic system, and subsequently into the body ( 26,27 ). Along the basolateral membrane of the enterocyte, CE gets to be assembled into the core of chylomicron particles and be secreted into the lymph in a microsomal transfer protein (MTP)-dependent manner.…”
Section: Intestinal Regulation Of Hdl Cholesterolmentioning
confidence: 99%